El impacto de la reforma educativa durante el gobierno militar de Juan Velasco Alvarado en la educación peruana (1968-1975) - Trejo Broncano, Ana Lucía (2022)
The purpose of this professional sufficiency job was to analyze the characteristics of the impact of the educational reform during the Military Government of Juan Velasco Alvarado in Peruvian education from 1968 to 1975. In such a way that we start by building a political, economic and social context of the aforementioned period. _x000D_ Equivalently, to explain the legislative bases of the Peruvian educational reforms preceding the 1972 one and the one_x000D_ that corresponds to our object of study. Subsequently, make a reflection on the role of intellectuals in the course of the educational reform of 1972. With the compilation of primary and secondary sources they have allowed to capture an outline of Peruvian society between 1968 and 1975, and direct us to the study of the causes and consequences of the Peruvian educational reform of 1972 implemented by the aforementioned military president